Emotional labor and burnout among hotel frontline employees in the Philippine tourism - Chizanne Sarabia Larena (Ho Chi Minh City Open University Journal of Science - Social Sciences)
Emotional labor is a quality service indicator that demands control of emotions and a display of facial expressions. This study investigated the psychosocial dimensions of emotional labor and burnout among hotel frontline employees in the tourism industry. The participants were frontline employees (n = 302) selected through stratified random sampling technique. To analyze the data, frequency distribution, percentage, means, standard deviation, Pearson Product Moment Correlation Coefficient, and Stepwise Regression were utilized. Results show that there is a significant relationship between emotional labor and burnout. Specifically, it reveals that surface acting, but not deep acting, is significantly related to burnout. Hotel frontline employees’ display of emotion-regulated work can be exasperating, and emotional labor, over time, contributes to burnout. Surface acting is a painstaking effort, leaving the front-liner more tired. Deep acting is a natural tendency among Filipinos to empathize with client’s needs. Nevertheless, managing emotional state is necessary in one-on-one mutual consultation with client service, otherwise, when not appropriately intervened, it will lead to unfavorable mental health concerns, such as burnout. Hence, periodic psychosocial training, cognitive techniques, and reframing of mind are helpful strategies to help front-liners control their emotions.